Osteoporotic Vertebral Fracture Prevalence Varies Widely Between Qualitative and Quantitative Radiological Assessment Methods: The Rotterdam Study. (6th September 2017) - Oei, Ling; Koromani, Fjorda; Breda, Stephan J; Schousboe, John T; Clark, Emma M; van Meurs, Joyce BJ; Ikram, M Arfan; Waarsing, Jan H; van Rooij, Frank JA; Zillikens, Maria C; Krestin, Gabriel P; Oei, Edwin HG; et al.
ABSTRACT: Accurate diagnosis of vertebral osteoporotic fractures is crucial for the identification of individuals at high risk of future fractures. Different methods for radiological assessment of vertebral fractures exist, but a gold standard is lacking. The aim of our study was to estimate statistical measures of agreement and prevalence of osteoporotic vertebral fractures in the population‐based Rotterdam Study, across two assessment methods. The quantitative morphometry assisted by SpineAnalyzer® (QM SA) method evaluates vertebral height loss that affects vertebral shape whereas the algorithm‐based qualitative (ABQ) method judges endplate integrity and includes guidelines for the differentiation of vertebral fracture and nonfracture deformities. Cross‐sectional radiographs were assessed for 7582 participants aged 45 to 95 years. With QM SA, the prevalence was 14.2% (95% CI, 13.4% to 15.0%), compared to 4.0% (95% CI, 3.6% to 4.5%) with ABQ. Inter‐method agreement according to kappa (κ) was 0.24. The highest agreement between methods was among females (κ = 0.31), participants age >80 years (κ = 0.40), and at the L1 level (κ = 0.40). With ABQ, most fractures were found at the thoracolumbar junction (T12 –L1 ) followed by the T7 –T8 level, whereas with QM SA, most deformities were in the mid thoracic (T7 –T8 ) and lower thoracic spine (T11 –T12 ), with similar number of fractures in both peaks. Excluding mild QM SA deformities (grade 1 with QM) from the analysis increased, the agreement between the methods from κ = 0.24 to 0.40, whereas reexamining mild deformities based on endplate depression increased agreement from κ = 0.24 to 0.50 ( p <0.001). Vertebral fracture prevalence differs significantly between QM SA and ABQ; reexamining QM mild deformities based on endplate depression would increase the agreement between methods. More widespread and consistent application of an optimal method may improve clinical care. © 2017 American Society for Bone and Mineral Research.